Carbon-chain molecules in molecular outflows and Lupus I region – new producing region and new forming mechanism. Issue 1 (25th June 2019) - Wu, Yuefang; Liu, Xunchuan; Chen, Xi; Lin, Lianghao; Yuan, Jinghua; Zhang, Chao; Liu, Tie; Shen, Zhiqiang; Li, Juan; Wang, Junzhi; Qin, Sheng-Li; Kim, Kee-Tae; et al.
Abstract: Using the new equipment of the Shanghai Tian Ma Radio Telescope, we have searched for carbon-chain molecules (CCMs) towards five outflow sources and six Lupus I starless dust cores, including one region known to be characterized by warm carbon-chain chemistry (WCCC), Lupus I-1 (IRAS 15398-3359), and one TMC-1 like cloud, Lupus I-6 (Lupus-1A). Lines of HC3 N J = 2 − 1, HC5 N J = 6 − 5, HC7 N J = 14 − 13, 15 − 14, 16 − 15, and C3 S J = 3 − 2 were detected in all the targets except in the outflow source L1660 and the starless dust core Lupus I-3/4. The column densities of nitrogen-bearing species range from 10 12 to 10 14 cm −2 and those of C3 S are about 10 12 cm −2 . Two outflow sources, I20582+7724 and L1221, could be identified as new carbon-chain-producing regions. Four of the Lupus I dust cores are newly identified as early quiescent and dark carbon-chain-producing regions similar to Lup I-6, which together with the WCCC source, Lup I-1, indicate that carbon-chain-producing regions are popular in Lupus I which can be regard as a Taurus-like molecular cloud complex in our Galaxy. The column densities of C3 S are larger than those of HC7 N in the three outflow sources I20582, L1221, and L1251A. Shocked carbon-chain chemistry is proposed to explain the abnormal high abundances of C3 S compared with those of nitrogen-bearing CCMs. Gas-grain chemical models support the idea that shocks can fuel the environment of those sources with enough S + thus driving the generation of S-bearing CCMs.